1996
DOI: 10.1017/s0263675100001988
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the Exeter Book of Old English poetry

Abstract: Exeter, Cathedral Library, 3501, fols. 8–130, the celebrated Exeter Book of Old English Poetry, preserves approximately one-sixth of the surviving corpus of Old English verse, and its importance for the study of pre-Conquest vernacular literature can hardly be exaggerated. It is physically a handsome codex, and is of large dimensions for one written in the vernacular: c. 320 × 220 mm, with a written area of c. 240 × 160 mm (see pl. III). In contrast to many coeval English manuscripts, particularly those in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Work by Klinck (1992, 13-21) on the language of some of the Exeter Book's texts suggests that they originated in different parts of England at different times, and work by Muir (2000, I: 16-25) on the compilation of the manuscript holds open the possibility of its copying from a similar or identical codex that is now lost. The Exeter Book itself might have been inscribed at Crediton or Exeter, as Conner (1993, 48-94) has argued; or it might have been made at Canterbury, or Glastonbury, before bishop Leofric acquired it, as Richard Gameson (1996) and Robert M. have suggested. Work on other Old English text types, especially hagiography, likewise suggests the more general availability of vernacular works exploring the different gendering of women (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Work by Klinck (1992, 13-21) on the language of some of the Exeter Book's texts suggests that they originated in different parts of England at different times, and work by Muir (2000, I: 16-25) on the compilation of the manuscript holds open the possibility of its copying from a similar or identical codex that is now lost. The Exeter Book itself might have been inscribed at Crediton or Exeter, as Conner (1993, 48-94) has argued; or it might have been made at Canterbury, or Glastonbury, before bishop Leofric acquired it, as Richard Gameson (1996) and Robert M. have suggested. Work on other Old English text types, especially hagiography, likewise suggests the more general availability of vernacular works exploring the different gendering of women (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Exeter's eleventh-century books are, as Richard Gameson observed, not just the product of a particular moment and reforming impulse, but rather a reflection of the ongoing commitment of Leofric and his two successors to establishing a basic "working" collection for their cathedral's canons. 157 Leofric's commitment to vernacular texts has understandably attracted considerable interest from Old English scholars and focussed attention on those manuscripts like the tenth-century collection of poetry known as the Exeter Book which make his library exceptional. 158 But the presence at Exeter in the later eleventh century of Usuard's text, a work which was widely copied in eleventh-and twelfth-century Lotharingia, fits with other indications that many of Exeter's late eleventh-century books were much more conventional and part of the European mainstream of post-Carolingian religious culture and canonical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to its focus on the depiction of Christ, the poem begins by establishing a conventional iconographic tableau of Doomsday, presenting a vivid description of the so-called signs of the coming Judgement which mark 'se micla daeg meahtan dryhtnes' ('the great day of the mighty Lord') (Muir 5 Conner (1993a) has put forward the strongest case for an Exeter provenance for the Exeter Book; this view has been supported by Muir (2000, p. 3), who has suggested that the book originates most likely from either Exeter or Crediton. Butler (2001) suggests a Glastonbury origin, while Gameson (1996) also contests the Exeter provenance. He acknowledges that both Glastonbury and Crediton are valid possibilities, but concludes that the origin of the book is 'best considered unknown' (p. 179).…”
mentioning
confidence: 99%